The Application Of The Model System The Achievement Of The Concept As An Attempt To Overcome The Misconceptions Language Indonesia - Annim Hasibuan; Ridho Kurniawan (CV. AFDIFAL MAJU BERKAH, 2021)
This research was conducted in class X MA Subulussalam Sumberjo. District Torgamba, Kabupaten Labuhanbatu Selatan. Object in this research is : the Application of the model system the achievement of the concept as an attempt to overcome the misconceptions of Indonesian Language, the Subject of the research is MA Subulussalam Sumberjo. The average value of student learning outcomes before the applied method of the System the achievement of concept is at 36,83% with the criteria is very low. Means the average value of the Indonesian Language students should be improved in the next cycle by applying the method of System achievement concept. The average value of learning outcomes of Indonesian students after applied System method is the achievement of the concept in the first cycle of 64,58 % with the criteria of being and in classical 63%. means the value obtained by the students have not yet reached the kertuntasan classical amounting to > 85%. The average value of learning outcomes of Indonesian students after applied System method is the achievement of the concept in the second cycle of 72,42% with very high criteria and in classical 88%. mean value learning outcomes the student has attained mastery in the classical. The increase in the average value of learning outcomes of Indonesian students from before action to the cycle of 27,75 %, and from cycle I to cycle II by 7.83 %. In cycle I, the average results of observation of the learning activities of students by 2,81 (70,24%) with good category, and in cycle II the average results of observation of the learning activities of students by 3,57 (89,29%) with very good category. In cycle I, the average observation of teacher activity is 3,83 with good category, and in cycle II the average results of the observation of teacher activity by 3.75 with a very good category